Corrigendum to “Efficient (S)-acetoin production in Saccharomyces cerevisiae by modulating α-acetolactate decarboxylase stereospecificity”. [Bioresource Technol. 434 (2025) 132767] - Cha, Seungwoo; Jang, Byeongseon; Lee, Daeyeol; Cho, Injae; Park, Wooyoung; Lee, Youngmin; Shin, Hyesoo; Kim, Minyoung; Sung, Changmin; Hahn, Ji-Sook (Elsevier BV, 2026)
The authors regret that the equal contribution of the first three authors was not indicated in the originally published version of this article. Seungwoo Cha, Byeongseon Jang, and Daeyeol Lee contributed equally to this work and should be considered co-first authors. The authors would like to apologise for any inconvenience caused.